Comparison of Pbl (Project Based Learning) Models with Pbl (Problem Based Learning) Models to Determine Student Learning Outcomes and Motivation - Simbolon, Redina; Koeswanti, Henny Dewi (Universitas Pendidikan Ganesha, 2020)
The problems that underlie this research are low learning outcomes and a lack of student motivation to learn, so a learning model is needed to improve the quality of the process and learning outcomes. This study aimed to analyze the comparison between the PJBL model of the PBL model on student motivation and learning outcomes. This research is a literature study with the research subject, comparing the PBL learning model with PJBL. The data collection method used is descriptive literature to find PJBL and PBL through reliable research data from other people. The data obtained were analyzed using data reduction, data presentation, and data conclusion. This study indicates that the PJBL model is superior in increasing student motivation and learning outcomes to the PBL model because PJBL can directly encourage students' motivation, which will automatically improve student learning outcomes. This study concludes that PJBL is superior to PBL in determining student learning outcomes and motivation. This research implies that apart from getting the PBL and PJBL models' results, it can provide an overview of the appropriate learning models for use in the learning process.